DAMPAK INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP PRILAKU ANAK - Siti Sahronih; Jatu Wahyu Wicaksono; Alrahmat Arif (Jurnal Pendidikan Dasar, 2020)
This study aims to determine the impact of the intensity of the influence of smartphones on children's behavior. The impact of the intensity of the influence of smartphones on children's behavior has a bad impact on children's behavior if it is not balanced with proper supervision. This research uses qualitative descriptive methods as a stage in carrying out research. This study was carried out in Cijoho by taking the subject of parents of children and children of smartphone users as the subject of the study. This research used data collection techniques including the observation, interview, documentation and recording stages. The results showed that the use of smartphones by children is based on individual needs, especially during the Covid-19 pandemic, children's learning is all online. Smartphones can be a means of learning and entertainment for children because they provide a lot of needed information. In addition to these beneficial things, the continued use of smartphones has a bad impact on children's behavior.